2019
DOI: 10.3389/fcomm.2019.00042
|View full text |Cite
|
Sign up to set email alerts
|

What Can Metaphor Tell Us About Experiences of Pregnancy Loss and How Are These Experiences Reflected in Midwife Practice?

Abstract: With the recent launch of the National Bereavement Care Pathways in the UK (http:// www.nbcpathway.org.uk/pathways/) that are designed to help professionals to support families in their bereavement after any pregnancy loss, there has been an increased interest in aligning the care provided to the needs that are expressed by the bereaved parents. In order to do this we need in-depth knowledge of these experiences. In this paper, we report findings from a study, conducted in England, that explored the ways in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 20 publications
3
33
0
Order By: Relevance
“…The parents in our study drew heavily on embodied metaphors to describe the strength and impact of the bereavement and ensuing emotions. The metaphors used had such a strong physical basis is in line with other studies that propose powerful, embodied metaphors can be the only device strong enough to to express emotions following traumatic experiences[32,33,3336]. Although metaphor is sometimes seen as a poetic device, operating solely at the level of language, we have demonstrated that it is inappropriate to see it as a surface-level linguistic phenomenon, particularly in the context of traumatic experiences.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The parents in our study drew heavily on embodied metaphors to describe the strength and impact of the bereavement and ensuing emotions. The metaphors used had such a strong physical basis is in line with other studies that propose powerful, embodied metaphors can be the only device strong enough to to express emotions following traumatic experiences[32,33,3336]. Although metaphor is sometimes seen as a poetic device, operating solely at the level of language, we have demonstrated that it is inappropriate to see it as a surface-level linguistic phenomenon, particularly in the context of traumatic experiences.…”
Section: Discussionsupporting
confidence: 85%
“…While altered perceptions of time over the course of the grieving process have been attested to in narratives following child loss [38], our findings indicate that changed experiences of time in the immediate aftermath of a loss may also have important implications for care. It is therefore important for HCPs to recognise that parents' emotional state may not be conducive to receiving and processing complex information, and they may need to be given the information more than once and/or in more than one format [32]. HCPs should demonstrate patience and sensitivity to parents' difficulties in processing information.…”
Section: Timementioning
confidence: 99%
“…However, it seems that Semino et al’s [ 7 ] study did not resolve how to identify the metaphorical symbolic activities or non-linguistic behaviors among the three levels of metaphors. To remedy this issue, Littlemore & Turner [ 10 , 11 ] conducted semi-structured interviews with women who experienced pregnancy loss. It was found that metaphor as a meaning-making phenomenon extended to the image (e.g., popcorn), symbolic behavior (e.g., beer-drinking), and ascribed meaning (e.g., a baby you know to be dead still needs “parenting”).…”
Section: Introductionmentioning
confidence: 99%
“…9 Findings from DBB evidence: (1) that there is considerable variation across England in the range of options that are offered 10 and (2) that people report effective communication as being important in shaping their experiences. 11 We use our own empirical research from this project to explore the ways in which the options for disposal were communicated to women who had experienced pregnancy loss. We bring these analyses together to provide as comprehensive an overview as possible of what might constitute effective (and less effective) communication with patients at a time of loss.…”
Section: Introductionmentioning
confidence: 99%